Gender Differences in Neurodegeneration, Neuroinflammation and Na+-Ca2+ Exchangers in the Female A53T Transgenic Mouse Model of Parkinson’s Disease - Costa, Giulia; Sisalli, Maria Jose; Simola, Nicola; Della Notte, Salvatore; Casu, Maria Antonietta; Serra, Marcello; Pinna, Annalisa; Feliciello, Antonio; Annunziato, Lucio; Scorziello, Antonella; Morelli, Micaela (Frontiers in Aging Neuroscience, 2020)
Middle-aged male mice expressing the human A53T variant of α-synuclein (A53T) develop dopamine neuron degeneration, neuroinflammation and motor deficits, along with dysfunctions of the mitochondrial Na+-Ca2+ exchanger (NCX) isoforms 1 (NCX1) and 3 (NCX3) in the nigrostriatal system. Since gender is thought to play a role in the aetiology of Parkinson’s disease (PD), we characterised neurochemical and behavioural alterations in middle-aged female A53T transgenic mice. We investigated the presence of dopaminergic degeneration, astrogliosis and microgliosis by means of immunohistochemistry for tyrosine hydroxylase (TH), glial fibrillary acidic protein (GFAP) and ionised calcium binding adaptor molecule 1 (IBA-1) in both the substantia nigra pars compacta (SNc) and striatum. In the same regions, we also evaluated the co-localisation of NCX1 in cells positive for IBA-1 and the co-localisation of NCX3 in TH-positive neurons and fibres. Furthermore, in both male and female mice we performed motor (beam walking test) and memory (novel object recognition and spontaneous alternation) tasks, together with tests to evaluate peripheral deficits (olfactory and stool collection tests). Female A53T transgenic mice displayed degeneration of nigral dopaminergic neurons, but neither microgliosis nor astrogliosis in the SNc and striatum. Moreover, female A53T transgenic mice displayed co-localisation between NCX1 and IBA-1 positive cells in the striatum but not SNc, whereas no co-localisation occurred between NCX3 and TH-positive terminals or neuronal bodies in the nigrostriatal system. Furthermore, female A53T transgenic mice showed increased crossing time in the beam walking test, but neither memory nor peripheral deficits, whereas male A53T transgenic mice displayed motor, memory and peripheral deficits. Results obtained here in female mice, which differ from those previously observed in males, suggest a dissimilar influence of NCX1 and NCX3 on dopaminergic function in female and male A53T transgenic mice, strengthening the validity of these mice as a model for studying the etiological factors of PD.